Multidisciplinary approach in treatment of spacing: Orthodontic treatment and partial ve-neers using the injectable composite resin technique - Ljubičić Miloš; Živković Marija (Serbian Medical Society - Dental Section, Belgrade, 2021)
Introduction Patients with orthodontic diagnosis of spacing most often require a multidisciplinary approach, which includes orthodontic and following restorative treatment to enhance the esthetic outcome. The aim of this case report is to present management of spacing in the anterior region by orthodontic treatment followed by partial veneers using the injectable composite resin technique. Case report In this case, leveling and alignment of dental arches and stable occlusion was achieved during orthodontic treatment, with the correction of upper and lower incisor inclination and closing the diastemas. Intraoral and extraoral esthetic parameters were evaluated on the photographs, and partial veneers on lateral incisors and canines were designed for the wax-up model. In the injectable composite resin technique, the silicone index was used to transfer the wax-up to composite restorations. The highly filled injectable composite resin was injected through the silicone index and light-cured. The restoration required only gentle polishing due to the great precision of the index. Discussion Post-orthodontic recontouring in the anterior region is mostly done by direct composite restorations because they are cost-effective, minimally invasive, and the procedure is relatively simple. The injectable resin composite technique can be a solution for the same indication since it is less technique sensitive and gives predictable and great esthetic results, mostly without tooth preparation. Conclusion Management of anterior spacing in adult patients requires a comprehensive approach for optimal esthetic and functional results. In this case, orthodontic treatment was followed by partial veneers on lateral incisors and canines, using the injectable composite resin technique as a simple and predictable solution for minor restorative interventions to solve morphological tooth abnormalities in the esthetic smile zone.